pengaruh kualitas produk, harga dan nkualitas pelayanan terhadap kepuasan konsumen - Rozi, Moh. Farid Atho’illah Fahrur; sukaris, Sukaris (Jurnal Mahasiswa Manajemen, 2020)
This study aims to analyze the effect of product quality, price and service quality on consumer satisfaction at Katon Ayu Wedding Organizer Gresik. This study uses a quantitative approach. The population in this study all consumers in Gresik Katon Ayu Wedding Organizer amounted to 150 people while the sample was 110 people and there were 10 people who did not meet the researcher’s criteria, the method used by purposive sampling researchers with the provisions of respondents who had chosen an exelent building package and luxury home package at Katon Ayu Wedding Organizer. The data analysis technique used is multiple regression analysis. Regression results obtained t count 9.495 while t table 1.985 therefore product quality affects consumer satisfaction at Katon Ayu Wedding Organizer Gresik. The variable price has -4,180 while t table 1,985 influences consumer satisfaction at Katon Ayu Wedding Organizer Gresik. The service quality has a t count of 7.225 while the t table of 1,985 affects consumer satisfaction at Katon Ayu Wedding Organizer Gresik. Product quality, price and service quality variables have a simultaneous and significant influence on customer satisfaction